Hybridization Implementation Of Electronic Land Information Service Policy - Asrofi, Asrofi; Rulinawaty, Rulinawaty; Yumiati, Yumiati (International Journal of Law Policy and Governance, 2025)
This research is a qualitative exploratory research with involved observation (vershtehen) which aims to explore and analyze the hybridization of policy implementation of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 19 of 2020 concerning electronic land information services in Bengkulu City, Bengkulu Province. Data collection was carried out using observation, documentation and in-depth interviews (indept interviews). The variables studied were developed from Van Meter and Van Horn (1975) including policy standards and objectives, resources, communication and inter-organizational activities, characteristics of implementing agents, environmental, economic, social and political conditions, attitudes of implementers.... The collected data will be analyzed using a triangulation analysis model with the help of Nvivo 12 application software. This study found that the regulation of electronic land information services has not regulated technical matters so that its implementation requires interpretation. Employees and implementing agents such as PPAT, Surveyors need technical guidance so that the policy implementation target is achieved. In addition, there are limited skilled human resources and internet network infrastructure are the main factors that hinder the hybridization process of land administration public policy implementation. The lack of commitment and support from the Government and the non-optimal institutional coordination mechanism for policy implementation have relatively minimal impact on the non-optimal socialization which makes the level of public understanding of electronic land information services very minimal. This has an impact on community resistance to implementing the electronic land information service policy.